Distal versus proximal arm tremor in multiple sclerosis assessed by visually guided tracking tasks. - Liu, X; Miall, R; Aziz, T; Palace, J; Stein, J (1999)
OBJECTIVES: To compare action tremor (AT) during manual tracking in normal subjects and patients with multiple sclerosis with tremor (MS-tremor group) and without tremor (MS-no tremor group), and to differentiate tremor occurring predominantly around the distal joint from that involving the proximal joints of the arm. METHODS: Subjects performed both a visually guided ramp tracking task using wrist flexion/extension and a whole arm circle tracking task using shoulder movement. Action tremor at the wrist or shoulder was computed as the SD of the tracking velocity. The ratio of wrist:arm tremor was then calculated to differentiate distal from proximal tremor in the tested arm. Frequency spectra of the records were also examined. RESULTS: During wrist tracking, AT in patients with multiple sclerosis contained a major frequency component at 4-5 Hz; the frequency was slightly lower during whole arm tracking. The ratio of wrist:arm tremor was significantly higher in the MS-tremor group. Of 12 tested arms, eight had tremor significantly weighted towards the distal joint, only one towards the proximal joint, and three had a ratio inside the control range. CONCLUSIONS: AT in the arms of patients with multiple sclerosis can be effectively differentiated into proximal or distal using these two different tracking tasks. Despite the variability of the effects of multiple sclerosis, most of the AT was distal rather than proximal in this group of patients. Possibly conduction block along the corticocerebellocortical pathways caused this distal tremor.